Challenges in HIV Vaccine Research for Treatment and Prevention - Ensoli, Barbara; Cafaro, Aurelio; Monini, Paolo; Marcotullio, Simone; Ensoli, Fabrizio (Frontiers in Immunology, 2014)
Many attempts have been made or are ongoing for HIV prevention and HIV cure. Many successes are in the list, particularly for HIV drugs, recently proposed also for prevention. However, no eradication of infection has been achieved so far with any drug. Further, a residual immune dysregulation associated to chronic immune activation and incomplete restoration of B and T cell subsets, together with HIV DNA persistence in reservoirs, are still unmet needs of the highly active antiretroviral therapy (HAART), causing novel “non-AIDS related” diseases that account for a higher risk of death even in virologically suppressed patients. These “ART unmet needs” represent a problem, which is expected to increase by ART roll out. Further, in countries such as South Africa, where 6 millions of individuals are infected, ART appears unable to contain the epidemics. Regretfully, all the attempts at developing a preventative vaccine have been largely disappointing. However, recent therapeutic immunization strategies have opened new avenues for HIV treatment, which might be exploitable also for preventative vaccine approaches. For example, immunization strategies aimed at targeting key viral products responsible of virus transmission, activation and maintenance of virus reservoirs may intensify drug efficacy and lead to a functional cure providing new perspectives also for prevention and future virus eradication strategies. However, this approach imposes new challenges to the scientific community, vaccine developers and regulatory bodies, such as the identification of novel immunological and virological biomarkers to assess efficacy endpoints, taking advantage from the natural history of infection and exploiting lessons from former trials. This review will focus first on recent advancement of therapeutic strategies, then on the progresses made in preventative approaches, discussing concepts and problems for the way ahead for the development of vaccines for HIV treatment and prevention